The Role of Savings and Loan Cooperatives in the Development of Micro, Small, and Medium Enterprises (MSMEs): (A Case Study on Sibotolungun Savings and Loans Cooperative (KSP) in West Medan District) - Perkasa, Ripho Delzy; Safitri, Dwi; Lubis, Ismanora; Aimansyah, Zaki (LPPPIPublishing, 2024)
The aim of this research is to identify the role of the Sibotolungun Savings and Loans Cooperative (KSP) in the development of Micro, Small and Medium Enterprises (MSMEs) in Medan Barat District and to determine the efforts of the Sibotolungun Savings and Loans Cooperative (KSP) in empowering the community economy in Medan Barat District . This research was conducted using qualitative analysis methods with data collection techniques through observation, interviews and documentation. The number of informants involved in this research was 4 people consisting of 1 KSP Sibotolungun employee and 3 MSME entrepreneurs. The results of this research show that: 1). The Sibotolungun Savings and Loans Cooperative (KSP) acts as a provider of capital financing for MSMEs, which contributes to economic growth and as an alternative savings institution other than banks. 2) KSP Sibotolungun’s Efforts to empower the community’s economy are carried out through providing counseling and Assistance to increase sales, so that entrepreneurs can remain competitive in the market.